Bedrock Stress Release Features on Manitoulin Island, Ontario - Karrow, Paul (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1993)
ABSTRACTManitoulin Island has large exposed bedrock plains underlain by Ordovician and Silurian carbonates. The generally flat-lying strata reveal evidence of rock stress reiased by faults at Little Current and by pop-ups elsewhere. Four pop-ups occur at widely separated localities on the island and several other small ridges may be pop-ups. Other bedrock stress-release features may be present but remain undiscovered in the extensively vegetated part of the island.